If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(6) = 2x Multiply -1 * 6 10 + -6 = 2x Combine like terms: 10 + -6 = 4 4 = 2x Solving 4 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4 + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 4 + -2x = 0 Add '-4' to each side of the equation. 4 + -4 + -2x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = 0 + -4 -2x = 0 + -4 Combine like terms: 0 + -4 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| X+x+1+x+2+x+3=132 | | 6x-4=74-7x | | (x-5)(-3x+7)-(x-5)=0 | | -17=-8 | | x^2+6x=x+3 | | 5y-6=2y+10 | | (X+8)+x=6 | | 8+2(x-2)=8 | | 6s-2t+3+7s+5t-9= | | 5x+39= | | 37+w=5w-2 | | X=2y-550 | | 9x+15=(3x+5) | | (8+10)-10=2x | | 2x-5y=-24 | | (X+8)+x=8 | | 3(e+1)=2(e-5) | | 84x^3-84x^2+84x-84=0 | | -63=-7x-9y*-7 | | -43x-23=15-72x | | 3sinx-2=-3 | | 36x-108=36+36x | | 5g+6+7g-10= | | vsquared+6v-16=0 | | h-8=12 | | -2x+8=-1x+3 | | 2x+10-3=-2x-2+1 | | 16+24x=4 | | v+6v-16=0 | | 8x+16=450+6 | | 5(x+20)=500-5x | | 2y^2-9y+2=0 |